Analisis SWOT Pemasaran Produk Qris Ultimate Automated Transaction (QUAT) Pada Bank BPD DIY Syariah - Trisanty, Aidha; Pawestri, Intan Dwi (STIE Ekuitas, 2022)
The development of digital technology today must be addressed appropriately by banks, including Islamic banking. Islamic banking must accommodate changes in customer behaviour that currently prefer speed, practicality and updates to technology to survive in increasingly tough competition. Bank BPD DIY Syariah, as the Sharia Business Unit of the Bank BPD DIY, is also required to meet customer needs in transaction services, one of which done through the QRIS Ultimate Automated Transaction Product. This study aims to find how the marketing of QUAT products carried out by BPD DIY Syariah as a strategy to improve services for customers. This study aims to find how the marketing of QUAT products carried out by BPD DIY Syariah as a strategy to improve services for customers. Research data is sourced from primary data (direct observation and interviews with related units) also secondary data (obtained through literature studies, journals, information and data on the internet, and other literature from companies). This research provides benefits in implementing digital-based marketing strategies for BPD DIY Syariah.